work alienation and its impact on Job Satisfaction Applied Research - فخري نور حسين; صالح مصطفى رعد (Journal of Economics and Administrative Sciences, 2020)
The research aims to determine the role of functional alienation and its impact on Job Satisfaction in General Motors Company, that were selected to apply the field side being an important company in Iraq, the problem was research with difficulty in employees adapt and their sense of alienation in their work which is reflected negatively on the level of satisfaction with work in company searched. A questionnaire was adopted as the main tool for data collection research which included (31) items distributed on (50) employees in the company selected, on a randomly chosen and based on the statistical program ready by (SPSS). Sample of this study was the most important findings of the research are the weak management of the company in reducing the alienation that staff is feeling at work, because that the possibilities and capacities of staff are not being properly exploited in General Motors Company, which increases their feeling Isolation and alienation at work. Important recommendations were of interest to the company’s management in terms of employees They feel bored in their performance, by reducing the routine. and encourage them to work collectively, and assign them to work that makes them feel important in the company, this role can limit the phenomenon of social isolation for employees in the work.